GC-MS Study of Bioactive Compound of Peperomia pellucida and Its Antibacterial Activity against Streptococcus mutans - Kuswati, Kuswati; Rosalinda, Julitha Dwi; Waluyo, Joko (Al-Hayat: Journal of Biology and Applied Biology, 2025)
Streptococcus mutans is the prior bacteria causing dental caries. Suruhan (Peperomia pellucida) may prevent dental caries due to its antibacterial bioactive content. This study aims to identify the bioactive profile of Suruhan ethanol extract and its antibacterial activity against Streptococcus mutans. Bioactive compounds were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). Antibacterial activity was tested through an inhibition test using the well-diffusion method, the Minimum Inhibitory Concentration (MIC) test, and the Minimum Bactericidal Concentration (MBC) test. The most detected compounds in Suruhan ethanol extract were n-eicosane, n-hexadecane, and glycerol. There are also antibacterial bioactives such as phenols, flavonoids, alkaloids, and terpenoids. Inhibition test of 500 mg/mL extract showed a clear zone of 8.25 mm diameter. The MIC and MBC values were 50 mg/mL and 100 mg/mL, respectively. Based on the results, Suruhan ethanol extract shows potential as an antibacterial, although its inhibitory effectiveness could be better.